Fungal Community Structural and Microbial Functional Pattern Changes After Soil Amendments by Oilseed Meals of Jatropha curcas and Camelina sativa: A Microcosm Study - Hu, Ping; Wu, Liangjun; Hollister, Emily B.; Wang, Autumn S.; Somenahally, Anilkumar C.; Hons, Frank M.; Gentry, Terry J. (Frontiers in Microbiology, 2019)
The meals after oil extraction from many oilseed crops have nutrition and biofumigation potential for land application. Oilseed meal (SM) from the dedicated bioenergy crop Jatropha curcas were implicated to contain compounds that have antibacterial properties on some soil pathogens. However, little is known about its effect on non-targeted soil microbial community, especially on fungi. SM from Camelina sativa contains moderate level of glucosinolates (GLS) and was under studied. To investigate soil fungal community responses to jatropha and camelina SMs, we conducted a lab based microcosm study, amending soil with 1% SMs of jatropha, camelina, flax, and biomass of wheat straw. Fungal community abundance and structure were analyzed based on the ITS region using qPCR and tag-pyrosequencing. Microbial functional changes were examined by community level physiological profile (CLPP) using Biolog assay. Both SMs from jatropha and camelina showed biofumigant properties and inhibited fungal proliferation. Jatropha SM significantly altered soil fungal community structures with lower fungal biodiversity and higher Chaetomium composition. Camelina SM amended soil promoted Fusarium proliferation. CLPP indicated sequential hierarchy for C metabolism in the oilseed-amended microcosms was generally complex C > phosphate-associated C > carboxylic acids > carbohydrates > amines > amino acids. No significant difference in CLPP was detected due to the type of SM treatment. Our data indicate that both SMs of jatropha and camelina have biofumigant properties and can differentially impact soil microbial communities, and the changes were relatively persistent over time. Microbial functional patterns on the other side were not impacted by SM type. Our study revealed biofumigant and nutritional influence of SMs from dedicated biofuel plants on soil microbial community. This information will help properly using jatropha and camelina SMs for pathogen control while minimizing their negative impacts on non-target microorganisms. However, further studies in the field are demanded to investigate their influences in real practice.